Tax Facilities for Investors in the Indonesian Capital from the Perspective of Justice and Legal Certainty - Eka Situmorang; Lilawati Ginting (International Journal of Society and Law, 2026)
The development of the Indonesian Capital City (IKN) requires substantial investment support, so the government is providing various tax incentives to attract investors. This policy aims to create a conducive investment climate, but on the other hand, it raises issues related to justice and legal certainty. The research questions are: (1) how are tax incentives regulated and implemented for investors in the IKN, and (2) how are these incentives viewed from the perspective of justice and legal certainty. This research uses a normative legal method with a statutory and conceptual approach. The legal materials used include regulations related to investment and taxation, as well as scientific literature in the form of journals and previous research results. Data collection techniques were conducted through literature studies and analyzed qualitatively and descriptively. The results show that the regulation of tax incentives in the IKN has been comprehensively regulated through various regulations, such as Law No. 25 of 2007 and Government Regulation No. 12 of 2023. However, implementation still faces obstacles in the form of policy inconsistencies, bureaucracy, and rapid regulatory changes. From a justice perspective, this policy has the potential to create inequality if not balanced by an equitable distribution of benefits. In terms of legal certainty, despite the existence of normative guarantees, practices in the field are not entirely consistent. In conclusion, tax facilities in the new capital city (IKN) do not fully meet the principles of justice and legal certainty. Therefore, regulatory strengthening, policy consistency, and effective oversight are needed to ensure this policy supports sustainable development.